ETHICAL ASPECT OF DIPLOMACY OF PROPHET MUHAMMAD (BASIC PRINCIPLE) - Indra Ari Fajari; Mohammad Muslih; Yuangga Kurnia Yahya (IAIN Bone, 2021)
Ethics is a branch of philosophy that discusses good and bad. This study still relevant to be examined and discussed until now, because by studying ethics, someone is able to find and obtain all the good things as well as to avoid the bad. However, ethics is often separated from the practice of life, one of them is modern diplomacy. Diplomacy is all the efforts made to regulate the relationship among nations. Thus, ethics of diplomacy in this sense can be meant as a basic principle or practice of diplomacy which is accountable, tolerant, and fair. Since this study is attempted to reveal how the ethics of diplomacy of Prophet Muhammad, then this study uses ethical perspective of Islam. In this approach, researcher used: first, the descriptive analysis methods to further explore the basic principle regarding diplomacy of Prophet Muhammad. Second, the critical analysis method to discover the implications and problems of the principles and practice of diplomacy in the modern era. Regarding this method, it was discovered that in fact the basic principle and practice of diplomacy of Prophet Muhammad are based on tawhīd.